Identifikasi Kandungan Volatil Ekstrak Etanol Benalu Alpukat (Dendrophthoe pentandra) Sebagai Kandidat Antibiotik Alami Tuberkulosis - Ainiyah, Roisatul; Nugroho, Endik Deni; Ardiansyah, Reza; Hamdani, Khoirul; Tarmudi, Imam; Kuswanto, Wawan; Hadi, Lukman (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Tuberculosis is an infectious disease that spreads through the air and is caused by the bacterium Mycobacterium tuberculosis. To combat it, synthetic drugs are commonly used, which can have adverse effects, making natural alternatives like avocado mistletoe (Dendrophthoe pentandra) necessary. This study aims to explore potential tuberculosis compounds from D. pentandra. The method used in this research is an exploratory descriptive method. The identification of compound content in the ethanol extract of D. pentandra leaves was performed using GC-MS, along with potential testing as an antituberculosis agent through in silico molecular docking. The research results showed that there were 13 volatile compounds contained in the ethanol extract of D. Pentandra leaves, predominantly consisting of propane, 1-methoxy, with a concentration of 9.39%. D. pentandra has the potential as a ClpP1P2 antituberculosis agent with four promising compounds:2-amino-1-(5-bromo-2-pyridinyl)-4-(2,4-dichlorophenyl)-7,7-dimethyl-5-oxo-1,4,5,6,7,8-hexahydro-3-quinolinecarbonitrile, stigmasterol acetate, Î²-sitosterol acetate, and Î³-sitosterol. PASSOnline predictions support the potential of ethanol extract of D. Pentandra leaves as anti-tuberculosis and anti-mycobacteria agent.